In silico structural and functional characterization and phylogenetic study of alkaline phosphatase in bacterium, Rhizobium leguminosarum (Frank 1879). (December 2019) - Yousafi, Qudsia; Kanwal, Saba; Rashid, Hamid; Khan, Muhammad Saad; Saleem, Shahzad; Aslam, Muhammad
Graphical abstract: Highlights: Phosphorus is one of the primary macronutrient of plants which is used in inorganic form Organic soil phosphorus can be converted to inorganic form by soil Rhizobium bacteria with the help of an enzyme alkaline phosphatase. Nine different strains of Rhizobium leguminosarum were selected for a detailed computational structural and functional characterization and phylogenetic studies of alkaline phosphatase. Seven out of nine strains were closely related and other two were distantly related. 3D models of the enzyme of nine strains were predicted and submitted to Protein Model Database (PMDB) for further use by researchers. Abstract: Phosphorus is one of the primary macronutrient of plants, which is present in soil. It is essential for normal growth and development of plants. Plants use inorganic form of phosphate but organic form can also be assimilated with the help of soil inhabiting bacteria. Alkaline phosphatase is an enzyme present in Rizobium bacteria. This enzyme is responsible for solubilization and mineralization of organic phosphate and makes it readily available for plants. In the present study, nine different strains of Rhizobium leguminosarum were selected for a detailed computational structural and functional characterization and phylogenetic studies of alkaline phosphatase. Amino acid sequences were retrieved from UniProt and saved in FASTA format for use in analysis. Phylogenetic analysis of these strains was done by using MEGA7. 3D structure prediction was performed by using online server I-Tasser. Galaxy Web and 3D Refine were used for structure refinement. The refined structures were evaluated using two validation servers, QMEAN and SAVES. Protein-protein interaction analysis was done by using STRING. For detailed functional characterization, Cofactor, Coach, RaptorX, PSORT and MEME were used. Overall quality of predicted protein models was above 80%. Refined and validated models were submitted into PMDB. Seven out of nine strains were closely related and other two were distantly related. Protein-Protein interaction showed no significant co-expression among the interaction partners.